Patient-reported outcome and muscle–tendon pain after periacetabular osteotomy are related: 1-year follow-up in 82 patients with hip dysplasia - Jacobsen, Julie Sandell; Søballe, Kjeld; Thorborg, Kristian; Bolvig, Lars; Storgaard Jakobsen, Stig; Hölmich, Per; Mechlenburg, Inger (Acta Orthopaedica, 2019)
Background and purpose — Larger prospective studies investigating periacetabular osteotomy (PAO) with patientreported outcome measures developed for young patients are lacking. We investigated changes in patient-reported outcome (PRO), changes in muscle–tendon pain, and any associations between them from before to 1 year after PAO. Patients and methods — Outcome after PAO was investigated in 82 patients. PRO was investigated with the Copenhagen Hip and Groin Outcome Score (HAGOS). Muscle–tendon pain in the hip and groin region was identified with standardized clinical tests, and any associations between them were analyzed with multivariable linear regressions. Results — HAGOS subscales improved statistically significantly from before to 1 year after PAO with effect sizes ranging from medium to very large (0.66–1.37). Muscle–tendon pain in the hip and groin region showed a large decrease in prevalence from 74% (95% CI 64–83) before PAO to 35% (95% CI 25–47) 1 year after PAO. Statistically significant associations were observed between changes in HAGOS and change in the sum of muscle–tendon pain, ranging from –4.7 (95% CI –8.4 to –1.0) to –8.2 (95% CI –13 to –3.3) HAGOS points per extra painful entity across all subscales from before to 1 year after PAO. Interpretation — Patients with hip dysplasia experience medium to very large improvements in PRO 1 year after PAO, associated with decreased muscle–tendon pain. The understanding of hip dysplasia as solely a joint disease should be reconsidered since muscle–tendon pain seems to play an important role in relation to the outcome after PAO.